Analysis of vitamin E content in pilot dairy products - Kárnyáczki, Zsuzsanna; Csanádi, József; Fenyvessy, József; Béri, Béla (Acta Agraria Debreceniensis, 2012)
Within the framework of Ányos Jedlik program we started an experiment on feeding anti-oxidants with dairy cows at Körös-Maros Biofarm Kft. The purpose of the experiment was to test whether vitamin E and selenium fed as feed-supplement have an effect on the composition of milk produced. Furthermore we examined the cheese and yoghurt made out of the milk to explore how much vitamin E and selenium is retained in the products after processing. Our goal is to develop such functional dairy product which can be part of the daily diet helping us to remain healthy. After analyzing the data we found out that the anti-oxidant fed to the cows resulted in elevated vitamin E and selenium levels in the milk and that these were retained in the cheese and yoghurt in relatively large amount.